2018
DOI: 10.3390/su10041110
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and Improvement of Lighting Efficiency in Working Spaces

Abstract: Lighting is an essential element for modern life, promoting a sense of wellbeing for users. However, bad illumination may produce health problems such as headaches and fatigue, among other vision problems. For that reason, this paper proposes the development of a smartphone-based application to help in lighting evaluation to guarantee the compliance of illumination regulations and to help increase illuminance efficiency, reducing its energy consumption. To perform this evaluation, the smartphone can be used as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 21 publications
0
6
0
3
Order By: Relevance
“…One possible explanation for this finding could be that wide shoulders may provide additional space for the driver, decreasing the probability of severe crashes. In addition, several studies have found partially similar results, that shoulder width is negatively associated with injury severity [20,42,45]. In dark conditions, the probability of major injury crashes decreases on dry surfaces.…”
Section: Roadway Characteristicsmentioning
confidence: 64%
“…One possible explanation for this finding could be that wide shoulders may provide additional space for the driver, decreasing the probability of severe crashes. In addition, several studies have found partially similar results, that shoulder width is negatively associated with injury severity [20,42,45]. In dark conditions, the probability of major injury crashes decreases on dry surfaces.…”
Section: Roadway Characteristicsmentioning
confidence: 64%
“…Some researchers advocated the integrated lighting control with occupancy sensors, photocells, and central control module for users' convenience and better experience [23]. A few researchers developed mobile applications for better user experience in terms of operability and mobility [18,30,31,36]. Evidence indicated that a well-designed mobile application can not only improve user experience, but also guarantee the compliance of illumination regulations and reduce energy consumption [36].…”
Section: Related Workmentioning
confidence: 99%
“…A few researchers developed mobile applications for better user experience in terms of operability and mobility [18,30,31,36]. Evidence indicated that a well-designed mobile application can not only improve user experience, but also guarantee the compliance of illumination regulations and reduce energy consumption [36]. In other studies, both illuminance and CCT were considered for improving users' visual comfort and wellbeing by adapting lighting environment to users' activity [26,32].…”
Section: Related Workmentioning
confidence: 99%
“…Intelligent lighting systems have been applied in the daily life of firms and workplaces [1]. It has become more prevalent to provide appropriate lighting system while minimizing the energy of the environment.…”
Section: Introductionmentioning
confidence: 99%